Evaluation of Four Rapid Tests for Detection of Hepatitis B Surface Antigen in Ivory Coast - Bamory Dembele; Roseline Affi-Aboli; Mathieu Kabran; Daouda Sevede; Vanessa Goha; Aimé Cézaire Adiko; Rodrigue Kouamé; Emile Allah-Kouadio; Andre Inwoley (Journal of Immunology Research)
Background. Hepatitis B virus (HBV) infection is a leading cause of liver disease worldwide. Hepatitis B surface antigen (HBsAg) rapid diagnostic tests (RDTs) could be an ideal tool for a large-scale HBV screening in settings with high endemicity but limited infrastructure. The aim of this study was to evaluate the diagnosis performance of such RDTs for screening HBV infection in Ivory Coast. Methods. From September 2018 to January 2019, a cross-sectional phase I evaluation study of RDTs was conducted in three laboratories of Abidjan (CeDReS, CNTS and IPCI), on a panel of 405 whole blood samples and 699 plasmas. Four HBsAg RDTs (Determine™ HBsAg, SD Bioline HBsAg WB®, Standard Q HBsAg® and Vikia HBsAg®) were evaluated. The diagnostic performance (sensitivity and specificity) was calculated in comparison to the reference sequential algorithms of two EIA tests (Dia.Pro HBsAg® one version ULTRA and Monolisa™ HBsAg ULTRA). Results. The Determine™ HBsAg and Vikia HBsAg® tests performed well, with 100% of sensitivity, specificity both on plasma and on whole blood. For SD Bioline HBsAg WB® and Standard Q HBsAg®, the specificities were 99.8% and the sensitivities 99.3% and 97.1% respectively. Finally, there were a total of 19 false negative results: 3 with SD Bioline HBsAg WB® and 16 with Standard Q HBsAg®. Conclusion. Determine HBsAg® from Alere and Vikia HBsAg® from Biomérieux are the most suitable RDTs for screening for HBV in Ivory Coast. A phase II evaluation must be initiated.